EDUCATION FOR SUSTAINABLE DEVELOPMENT (EfSD): GAP OF INDICATORS FOR ENVIRONMENTAL LITERACY ACHIEVEMENT IN THE MIDDLE SCHOOL CURRICULUM - Widy - Anggraini; Puguh - Karyanto; Sarwanto - Sarwanto (EDUSAINS, 2018)
EDUCATION FOR SUSTAINABLE DEVELOPMENT (EfSD): KESENJANGAN INDIKATOR UNTUK PENCAPAIAN LITERASI LINGKUNGAN DALAM KURIKULUM SEKOLAH MENENGAH PERTAMAAbstractEnvironmental education is one way to empower the environment where literacy can support sustainable development programs known as Education for Sustainable Development (EfSD). This study aimed to analyze the environmental literacy indicators in the curriculum of middle schools. The lesson plan in the middle school became the main subject for document analysis. This research is evaluation research. The data were collected with non-test techniques in the form of interviews and documentation. Qualitative analysis in the form of a matrix became the instrument used to analyze the gap of the indicators of the ideal knowledge and those of the aktual knowledge. The results indicated that out of 20 aktual indicators, there were 10 irrelevant indicators with the ideal indicators according to the New Ecological Paradigm (NEP) and the ecological concept according to Lewinsohn. The gap between indicators of achieving environmental literacy can be overcome by substituting the overall ecological concept in the lesson plan for the environment-related material. The existence of a strong ecological concept is expected to be the initial provision for students to empower environmental literacy.AbstrakPendidikan lingkungan menjadi salah satu cara untuk memberdayakan literasi lingkungan sehingga dapat mendukung program pembangunan berkelanjutan atau dikenal sebagai Education for Sustainable Development (EfSD). Penelitian ini bertujuan untuk menganalisis kesenjangan indikator pencapaian literasi lingkungan dalam kurikulum sekolah menengah pertama (SMP). Rencana perangkat pembelajaran di SMP menjadi subjek utama dokumen yang dianalisis. Jenis penelitian yang digunakan adalah penelitian evaluasi (evaluation research). Pengumpulan data dilakukan dengan teknik non-tes berupa wawancara dan dokumentasi. Analisis kualitatif dalam bentuk matriks menjadi alat yang digunakan dalam menganalisis kesenjangan indikator pengetahuan ideal dengan indikator aktual. Hasil penelitian menunjukkan bahwa dari 20 indikator aktual terdapat 10 indikator yang tidak relevan dengan indikator ideal menurut New Ecological Paradigm (NEP) dan konsep ekologi menurut Lewinsohn. Kesenjangan antara indikator pencapaian literasi lingkungan dapat diatasi dengan mensubstitusi konsep ekologi secara utuh kedalam rencana pelaksanaan pembelajaran untuk materi yang berhubungan dengan lingkungan. Adanya konsep ekologi yang kuat diharapkan dapat menjadi bekal sejak dini bagi siswa untuk memberdayakan literasi lingkungan.